An Integrated View of the Molecular Recognition and Toxinology From Analytical Procedures to Biomedical Applications - Rádis Baptista, Gandhi (IntechOpen, 2013)
Molecular Toxinology has been consolidated as a scientific area focused on the intertwined description of several aspects of animal toxins. In an inquiring biotechnological world, animal toxins appear as an invaluable source for the discovery of therapeutic polypeptides. Animal toxins rely on specific chemical interactions with their partner molecule to exert their biological actions. The comprehension of how molecules interact and recognize their target is essential for the rational exploration of bioactive polypeptides as therapeutics. Investigation on the mechanism of molecular interaction and recognition offers a window of opportunity for the pharmaceutical industry and clinical medicine. Thus, this book brings examples of two interconnected themes - molecular recognition and toxinology concerning to the integration between analytical procedures and biomedical applications.